Assessing the Tendencies and Structural Changes in the Foreign Economic Activity of the Cities of Region - Zhabynets Olha Yo. (Bìznes Inform, 2020)
The article assesses the tendencies and structural changes in the foreign economic activity of the cities of regional significance of the Western region of Ukraine. In particular, the main indicators of foreign economic activity of cities for the period 2012-2017 were analyzed; cities were ranked by the rate of growth of exports, imports and foreign direct investments, as well as the proportion of exports of goods and services in the overall exports of cities, the speed and intensity of structural transformations. Changes in the structure of foreign economic activity of cities and in the level of their import dependence are identified. The problems defining the status of foreign economic activity in the cities of regional significance of the Western region of Ukraine are outlined and the key directions of their solution are suggested. It is determined that the structure of exports of the analyzed cities during 2012–2017 is represented by the prevailing share of commodity exports (on average above 80% in 2012 and above 75% in 2017). Against the background of the growth of exports of services, the share of exports of goods in 2017 decreased slightly, but remained a significant component of export activity. The growth of export volumes in the cities of regional significance of the Western region of Ukraine and the decrease of import dependence of their economies are proved. Significant contribution of the cities of regional significance to increasing the exports of services and reducing the volume of foreign direct investment to the economy of the vast majority of cities of the Western region of Ukraine are justified.